PENINGKATAN HASIL BELAJAR SISWA PADA PEMBELAJARAN PKn DENGAN MENGGUNAKAN MODEL PROBLEM BASED LEARNING (PBL) DI SEKOLAH DASAR - Ramadia, Ramadia; Zuardi, Zuardi; Sukma, Elfia (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
This research is motivated by the low of student learning outcomes in class SD Negeri 06 Padang Laweh Malalo, Tanah Datar Regency. This study aim to describe the improvementof student learning outcomes on learning Civic applying the model Problem Based Learning on the fourth grade student Primary school 06 Padang Laweh Malalo Tanah Datar Regency Type of research is PTK by using qualitative and quantitative approach. The result of student learning cycle I 71,39 increased to 84,85 in cycle II. Therefore learning of Civics by applying the Problem Based Learning model on can improve the learning outcomes of Civics students grade V SD Negeri 06 Padang Laweh Malalo, Tanah Datar Regency.Key Word: Result of study, PKn, Problem Based Learning Model.